Bachelor's and master's degrees integrated in Portugal in the area of computing: a global vision with emphasis on programming UCS and programming languages used - Sobral, Sónia Rolland (2018)
The creation and maintenance of courses (1st cycle and integration 1st and 2nd cycle) in computer science is of concern to those responsible. The area is in constant development and, despite the need for very specialized technicians and almost unemployment zero, it seems that it is not in the minds of most students who finish high school. This article describes how secondary education works in Portugal, as well as the entrance to the Portuguese higher education. With this study we were able to verify which courses have the most demand and, on the other hand, those that do not constantly fill all the vacancies. In this study we verified that in the year 2016-2017 the students who intend to join the upper insino had 122 courses: 106 Lic-1º cycle, 15 Integrated Masters and 1 Preparation. In other words, the choice was made from the Area of Technologies and returned links to information about 193 courses. We extract courses in which in its denomination it had the content comput * and informát *. We also added eight that seemed relevant to us as Management and Information Systems or information technologies. The basis of our study consists of a 122 courses of 66 different intuitions. We highlight the institutions of higher education (public and private), denomination of courses and type (1st cycle, integrated masters or preparation). From these courses we verify the proofs of access are (with view to numerous clausulus). The private Universities give little information: so we put them way out; for the rest: only 59 courses filled all the vacancies. We will study these 59 courses in more detail: institutions and different names. Of these, only 46 have course unity are available on-line. We have studied in detail the curricular units of the first two semesters. We extract the number of course unit and programming languages (which are) and study those course unity contents. Of the 46 courses we presented we extracted ten, the top 10. The choice of these and not others is related to the number of places being higher than the other courses, as well as the entry notes. From this 10 courses we will study course plans, as well as giving emphasis to course unity those who use programming languages: what programming languages, paradigms, and how many are used. In this way we get an overview of the curricula of computer courses in Portugal, namely what refers to paradigms and programming languages?